2000
DOI: 10.1097/00001756-200008210-00031
|View full text |Cite
|
Sign up to set email alerts
|

Motion processing in autism

Abstract: We report that motion coherence thresholds in children with autism are significantly higher than in matched controls. No corresponding difference in form coherence thresholds was found. We interpret this as a specific deficit in dorsal stream function in autism. To examine the possibility of a neural basis for the perceptual and motor related abnormalities frequently cited in autism we tested 23 children diagnosed with autistic disorder, on two tasks specific to dorsal and ventral cortical stream functions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(115 citation statements)
references
References 9 publications
6
104
2
Order By: Relevance
“…This was indeed what we found using a complex low-level auditory discrimination paradigm, as the gain in speech perception from amplitudemodulated pink noise (relative to continuous pink noise) was significantly smaller in subjects with autism than in controls. This finding suggests that subjects with autism have a diminished ability to integrate auditory information fragments present in temporal dips, analogous to a diminished ability to integrate the movements of dots in random dot kinematograms in the visual domain (Spencer et al 2000). However, we found no difference in the ability to integrate auditory information fragments present in spectral dips in ripple sounds.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…This was indeed what we found using a complex low-level auditory discrimination paradigm, as the gain in speech perception from amplitudemodulated pink noise (relative to continuous pink noise) was significantly smaller in subjects with autism than in controls. This finding suggests that subjects with autism have a diminished ability to integrate auditory information fragments present in temporal dips, analogous to a diminished ability to integrate the movements of dots in random dot kinematograms in the visual domain (Spencer et al 2000). However, we found no difference in the ability to integrate auditory information fragments present in spectral dips in ripple sounds.…”
Section: Discussioncontrasting
confidence: 58%
“…interrupts transient auditory memory formation), such that subjects with autism and controls resort to the same processing strategy. Several studies had already found enhanced simple lowlevel visual processing (O'Riordan et al 2001;Plaisted et al 1998) and spared (Spencer et al 2000;Blake et al 2003) or diminished complex low-level visual processing (Milne et al 2002). In the auditory domain, enhanced simple low-level processing had been reported for pitch discrimination and chord disembedding (Bonnel et al 2003;Heaton 2003), in which perceptual performance depends on spectral processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, elevated motion coherence thresholds in observers with highfunctioning autism (HFA), but not AS, have also been documented with Glass patterns (Glass, 1969), randomized dot arrays depicting correlated dot pairs (Spencer & O'Brien, 2006;Tsermentseli et al, 2008). In sum, the results of eight psychophysical studies (Davis et al, 2006;Gepner & Mestre, 2002;Gepner et al, 1995;Milne et al, 2002;Pellicano et al, 2005;Spencer & O'Brien, 2006;Spencer et al, 2000;Tsermentseli et al, 2008) converge in suggesting that the visual analysis of motion, whether in translating random dot patterns or expanding and contracting luminance gratings, is compromised in observers with ASD (Table 1). Because the perception of coherent motion in these random dot displays requires a global integration of motion information across many points, the threshold atypicalities described above may be consistent with a decreased reliance on global motion processes and/ or an increased reliance on local motion processes.…”
Section: Comparisons Of Visual Motion Processingmentioning
confidence: 88%
“…Several studies have now shown that individuals with ASCs show higher thresholds for the perception of motion coherence (e.g. Spencer et al 2000;Milne et al 2002;Pellicano et al 2005). Two proposals have been advanced for this relative insensitivity to motion coherence.…”
Section: Difficulties In Perceptionmentioning
confidence: 99%